Calculated contributors: IGO support for ethnopolitical organizations. Issue 2 (4th May 2019) - Asal, Victor; Heger, Lindsay; Stinnett, Douglas M.
ABSTRACT: Why do some organizations representing ethnic minorities receive outside diplomatic support from intergovernmental organizations (IGOs)? This article analyses ethnopolitical organizations in the Middle East from 1980 to 2004. The analysis explores two different possible answers. First, IGOs are guided by normative principles and are inclined to support ethnopolitical organizations that have democratic characteristics. Second, IGOs are guided by practical concerns, and choose to support those organizations that have the most influence. Although the analysis finds evidence for both the normative and strategic views, the variables associated with the strategic view have a larger substantive effect on the probability of support.